PENGARUH PENERAPAN ROAD PRICING PADA RUAS JALAN ARTERI PRIMER DI KOTA MANADO (STUDI KASUS: JALAN SAM RATULANGI - PERTIGAAN PIKAT) - Hajia, Muhammad Chaiddir; Rompis, Semuel Y. R.; Jansen, Freddy (JURNAL SIPIL STATIK, 2019)
Manado city with an area of 157.27 m2. This city continues to grow and develop along with the development of the world of tourism which is one of the mainstays in the economic sector. With the development of the tourism world, this is very influential in the development of the transportation world, especially ground transportation. Land transportation in Manado city is dominated by mikrolet, taxi and bus. Due to the rapid increase in vehicles and increasing congestion level, one solution to overcome supply and demand problems in Manado City is by implementing mass transit or road pricing. For structuring the solution because there is taxi online which also develops in big cities and one of them is Manado, this solution cannot be used as an alternative to decrease congestion problem so the solution in this study is to implement road pricing. This research began with data collection of manual traffic volume for 15 hours to be calibrated with time data take it for 3 days to get the alpha and beta values with the equation developed by The Bureau of Public Road. Then precede with analysis traffic loading uses the War drop I Balance principle and Solver's assistance is a facility from Microsoft Excel to load traffic to find out road volume. From the results of the sensitivity analysis it can be concluded that the road pricing price will be used is Rp. 2500, -Keywords : arteri primer, road pricing.